French Press on the Romanian and Bulgarian Presidency of the European Union - Antoanela-Paula Mureșan (CES Working Papers, 2019)
Bulgaria and Romania joined the European Union in 2007. For both of them, the taking over of the rotating presidency of the Council of the European Union has represented a crucial moment. Two former communist countries, east-central countries, have been in charge of the Council of the European Union. The article attempts to present some perception of the French press on the presidencies of these two countries, which has engendered a series of results indicating a subjectively different approach towards the Romanian and the Bulgarian presidencies of the Council of the EU. While the former has been regarded from a critical standpoint in the light of the internal political context, a more constructive view has been adopted in the case of the latter.
Keywords: 330; European Union; Romania; Bulgaria; Presidency of the Council of the European Union